Prevalence of performance-enhancing substance use and associated factors among Portuguese gym/fitness users - Tavares, Ana Sofia (2020)
Background: Nowadays, doping is not confined to elite sport, it is also spread throughout gymnasia and fitness centers, and it is seen as a public health concern. Studies focusing on performance-enhancing substances (PES) use among gym users are few and mostly concern the practice of bodybuilding and the use of anabolic-androgenic steroids (AAS), without providing information about social indicators to further explore why this specific population uses these substances. Objectives: To investigate the extent of PES use and examine the way social indicators, exercise profile and gym modalities influence the use of these substances among a sample of gym users. Methods: Cross-sectional descriptive study, among a convenience sample of 453 Portuguese gym users, recruited directly by five institutional gyms´ email and Facebook. Data were collected via a structured web-based survey, between October and November 2017. Multiple binary logistic regression, the Chi-Square test or Monte Carlo Simulation or Fisher’s Exact test were used. The odds ratios and their respective 95% confidence intervals were calculated. Results: 11,1% of gym users reported the use of prohibited PES, which varies significantly according to gender, education, exercise profile and type of practice. Gender was associated with the class of PES used. Polypharmacy was a common practice among users, increasing the risk of side effects. Peer effect and media appear to be strikingly important in the misuse of PES. Conclusion: Results provide precise insight into the specific factors associated with PES use, which could support prevention strategies in the gym/fitness context.